A study of container ship structures' ultimate strength under corrosion effects. (15th January 2017) - Cui, Jinju; Wang, Deyu; Ma, Ning
Abstract: Corrosion takes place in the life cycle of ships, resulting in degradation of structural strengths. Corrosion effects with uncertainty on ultimate strength for container ship structures are studied in this paper. On one hand, the ultimate strength of container ship hull girder subject to combined moments of bending and torsion is studied by Nonlinear Finite Element Analysis (NFEA), and the limit state of failure is derived through Minimum Square Error (MSE) technique based on a series of NFEAs, and the probabilistic characteristics under simultaneous uniform corrosions (however, with different scales) in longitudinal structures are studied for the cases of pure bending, pure torsion and combination of both, which can be a useful reference for the scheduled maintenance of container ships. On the other hand, the ultimate strength of bottom stiffened panel under longitudinal thrust derived from hogging conditions is studied considering effects of key factors such as initial deflection, element sizes, simplified boundary conditions, and lateral seawater pressure etc. Uniform and not simultaneous corrosion across different structures is studied, and surrogate models by Gaussian Process (GP) are built, and the corresponding ultimate strength probabilistic characteristics and its dependency on correlation between different structures' corrosion are studied. Highlights: Hull girder limit states under bending, torsion and combined moments, and the probabilistic characteristics are studied. The ultimate strength of stiffened bottom panel under longitudinal thrust is studied and is compared to benchmark. Effects of key factors such as initial deflection, element sizes, boundary conditions and lateral pressure are studied. Loss of stiffened panel's ultimate strength under corrosion follows similar probabilistic distributions with corrosion. In the case study of stiffened panel, simultaneous corrosion gives conservative ultimate strength evaluations.